How Web 2.0 Technologies Affect Business? - Attitudes of Top and Middle Managers in BiH Companies (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
The paper presents the results of empirical research on the impact of Web 2.0 technologies on a company's business. The research was conducted among top and middle managers in companies in Bosnia and Herzegovina. The results show that, although all respondents do not use the aforementioned technologies, they have a relatively positive opinion on the application of Web 2.0 technologies in business. According to their opinion, Web 2.0 technologies make the most important contribution to sharing of data and information in company and have a significant impact on the quality of communication, both internal and external. These results encourage further research on the application of Web 2.0 technologies in business and the use of all the advantages and benefits they can provide to someone actively using them.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.